An investigation of linearity and sensitivity of Fiber Bragg Grating sensors - Ahmed Tahir, Bashir (National Institute of Research and Development for Optoelectronics, 2009)
In this work, we investigate the linearity and sensitivity of Fiber Bragg Grating (FBG) sensors. A simple experimental setup comprising optical spectrum analyzer, tunable laser source and fiber grating may be utilized to obtain the wavelength shift and strain measurements. The sensing principle is based on tracking of Bragg wavelength shifts due to the change of loading conditions. The experiment was performed on a fiber grating bonded specimen plate made of Zinc. From the experiment, measure the wavelength shift and then axial strain corresponding to the variation of applied load/temperature change. Based on the results, a linear response has been observed between applied strain/temperature and Bragg wavelength shift throughout the measured region. It has also been demonstrated that the fiber Bragg grating system is more sensitive for 10cm sensor. The measured sensitivity of 10cm and 15cm sensor is 0.0011nm/µm and 0.0016nm/µm respectively at the same loading conditions. One can also anticipate 0.014nm grating wavelength expansion as a result of temperature change of 1°C to bare FBG fiber. The experimental results are also showing the capability of the proposed system to perform strain/temperature measurements.